Establishment of a CFD‐based kLa model in microtiter plates to support CHO cell culture scale‐up during clone selection. (3rd October 2018) - Wutz, Johannes; Steiner, Robin; Assfalg, Kerstin; Wucherpfennig, Thomas
Abstract : Microtiter plates are a common tool for clone selection in biopharmaceutical development. A way of visualizing and evaluating these systems and key processes parameters is the application of Computational Fluid Dynamics (CFD). CFD is a powerful tool for the modelling of hydrodynamics and mass transfer parameters. In this work, CFD was used to determine the specific surface area, the volumetric power input and the oxygen mass transfer coefficient k L a for two different microtiter plates with different scales (100 μL ‐ 5 mL). For this purpose, a new method of predicting the k L a is presented and calibrated with literature data. Scaling effects in shaken microtiter plates are evaluated by comparing two culture volume scales under various operating conditions. To test validity of these models, three different Boehringer Ingelheim Pharma proprietary CHO production cell lines with different growth characteristics were cultivated using the respective microtiter plates under different conditions until limitations in growth and viability were observable. The cell culture data then was compared to different parameters obtained by CFD. The calculated k L a values match the cell culture performance in the 96‐deepwell by predicting lowered oxygen transfer with increasing culture volume and decreasing orbital velocity. The same cells behave differently in the 6‐deepwell scale. Here, the overall larger shear stress might cause physical stress for the cells. The k L a model predicts overall higher shear rates for this system, supporting the experimental findings. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 2018